Importance of geotechnical soil properties for precision Forest activities in a karst area - Dindaroglu, Turgay; Vermez, Yasin; Gundogan, Recep; Yakupoglu, Tugrul; Gunal, Hikmet; Akay, Abdullah E. (Elsevier, 2024)
Some soil behaviors change significantly as water content varies over time. The particle size distribution of soils has a direct impact on mechanical properties such as soil water content, resistance to dispersion, swelling-shrinkage, fluidity, plasticity, and stickiness. This study was conducted to investigate the usability of Atterberg limits, consistency index and coefficient of linear extensibility (COLE) in the temporal planning of ecosystem restoration activities such as silvicultural interventions, tillage, afforestation, and the construction of forest roads, etc. Surface soil samples were collected from the sections numbered 263, 264, 266, 268, 317, 318, 319, 323, 324,325 and 366 of the degraded forest of the And & imath;r & imath;n forestry operations department. The COLE, liquid limit (LL), plastic limit (PL), plasticity index and consistency index values of soil samples were determined. The LL values ranged from 17.5 to 62.4%, the PL values from 8.2 to 46.8% and the PI values from 6.4 to 15.5. The highest COLE value (0.13) was recorded in the section 318, while the lowest COLE value (0.03) was in section 325.The LL and PL values have a positive linear relationship with clay and organic matter content. All sections have karstic characteristics, but the mechanical characteristics of the soils differ significantly between the sections. Silvicultural interventions carried out especially in section 318, which had the lowest consistency index (Ic = 0.70), and sections 263, 264, 317 and 319, where the consistency index is >2,should take mechanical properties into account, and the planting time intervals should be determined, accordingly for sustainable forestry.
Keywords: Atterberg limits; COLE; Precision forestry; Planting time; Soil tempering; Karst forest soil; Consistency index; Silviculture